THE EFFECT OF VARIOUS CONCENTRATIONS OF BUTYRIC ACID ON PERFORMANCE AND CARCASS PERCENTAGE OF BROILER - Abel, Ribka Natasia; Bebas, I Wayan; Sumadi, I Ketut (Buletin Veteriner Udayana, 2022)
This study aims to determine the effect of various concentrations of butyric acid on the performance and carcass percentage of broiler. This study used 24 broilers strain CP 707, PT. Charoen Pokphand and conducted in Penebel Village, Penebel District, Tabanan Regency, Bali Province. This study used a completely randomized design (CRD) with 4 treatments and 6 replications. The treatments were P0 (feed without butyric acid/control), P1 (feed added with 0.1% butyric acid), P2 (feed added with 0.2% butyric acid), and P3 (feed added with 0.3% butyric acid). The variables of this study were body weight gain, feed intake, feed conversion ratio (FCR), and carcass percentage of broiler. Data were analyzed using Analysis of Variance (ANOVA) and if there were differences, it was continued with Duncan's Multiple Range Test. The results showed that butyric acid with concentrations of 0.1%, 0.2%, and 0.3% had a significant effect on improving the performance of broilers. The application of various concentrations of butyric acid significantly affected the body weight gain of broilers, but had no significant effect on feed intake and feed conversion of broilers. Butyric acid with concentrations of 0.1%, 0.2% and 0.3% also had a significant effect in increasing the percentage of broiler carcasses.